Transfollicular enhancement of gel containing cationic niosomes loaded with unsaturated fatty acids in rice (Oryza sativa) bran semi-purified fraction - Aranya Manosroi (2018)
The 20 mM cationic niosomes composed of Tween61/cholesterol/CTAB at 1:1:0.5 M ratio which gave the best physical appearance, particle size, zeta potential and in vitro cytotoxicity were selected from six cationic niosomes prepared from various cationic lipids. The selected cationic niosomes were loaded with the semi-purified fraction 3 of Oryza sativa (OSF3) which gave the highest in vitro 5α-reductase inhibition activity. The physicochemical characteristics as well as transfollicular penetration through porcine skin by Franz diffusion cells of gel OSF3 niosomes, OSF3 niosomes, gel OSF3 and OSF3 solution were investigated. Gel containing niosomes loaded with OSF3 exhibited physical stability with 77.68% of gamma-linolenic acid, 85.34% of linoleic acid and 89.47% of oleic acid remaining for 3 months at 25 °C. In the skin, the OSF3 niosomes (120.27 ng/cm2) and gel OSF3 niosomes (118.17 ng/cm2) showed the highest cumulative amounts of the total unsaturated fatty acids (gamma-linolenic acid, linoleic acid and oleic acid) in comparing to those from the gel OSF3 (15.34 ng/cm2) and OSF3 solution (20.31 ng/cm2) of about 8 and 6 times, respectively. In the receiver compartment, the gel OSF3 niosomes (6.27 ng/cm2) exhibited lower cumulative amount of the total unsaturated fatty acids than that of the OSF3 niosomes (11.20 ng/cm2) of about 2 times. This study has suggested that gel containing OSF3 loaded in niosomes appeared to be the suitable system for topical anti-androgenic alopecia application because of the convenient use and high transfollicular penetration in the skin, but not in the receiving compartment with the advantage of low systemic effect. © 2012 Elsevier B.V. All rights reserved.